Lumbung Padi Kerinci Sebagai Objek Penciptaan Karya Seni Grafis Gaya Surealis - Jeki Aprisela H; Rajudin Rajudin (V-art: Journal of Fine Art, 2022)
The Kerinci Rice Barn is the object of this printmaking. The Kerinci rice barn was chosen as the object of creation because its existence is already threatened with extinction. In fact, the philosophical value of the Kerinci rice barn is very noble and profound. This printmaking is made in a surreal style. The concept of distortion is used to make the work more surreal. The idea behind this work is to use the Kerinci rice barn as an idiom to express oneself through art. The stages of the method in this creation are: contemplation, prototype, and forming. This printmaking work combines the hardboard cut technique with the stencil technique. The media used are acrylic paints and oil-based printing inks on canvas. The creation of this work has resulted in a work entitled "Menabung". This work measures 100 cm x 100 cm.